Intrinsically disordered linkers and terminal domains codrive aciniform spidroin self-assembly through liquid–liquid phase separation - Ruiqi Qin; Runze Yang; Shuixin Yu; Wei Guo; Hailong Cong; Yuzhe Ning; Cheng Chen; Daiwen Yang; Wensu Yuan; Zhi Lin (Proceedings of the National Academy of Sciences, 2025)
Aciniform silk is a remarkably tough and elastic protein fiber primarily used by spiders to wrap prey and construct the inner layers of egg sacs. While the formation of ampullate and eggcase silks has been extensively studied, the molecular mechanism underlying the self-assembly of the aciniform spidroin, AcSp1, remains poorly understood. Here, we demonstrate that the intrinsically disordered linkers of AcSp1 play a critical role in driving spidroin assembly through liquid–liquid phase separation in solution. The N-terminal domain (NTD) exhibits pH-independent dimerization over a physiological pH range (5.0 to 7.0) and undergoes concentration-dependent tetramerization. Quaternary structure of AcSp1-NTD shows a hierarchical assembly process mediated by both hydrophobic and electrostatic interactions, which enhances phase separation in both salt-free and salt-containing solutions. Finally, inspired by this mechanistic insight, we developed a fully aqueous spinning method to fabricate artificial aciniform fibers with excellent extensibility and toughness. These findings uncover a pivotal molecular strategy that transforms our understanding of diverse molecular mechanisms governing spidroin assembly and establish a foundation for designing and manufacturing elastic and tough silk-based biomaterials.